BdWRKY38 is required for the incompatible interaction of Brachypodium distachyon with the necrotrophic fungus Rhizoctonia solani. (19th September 2020) - Kouzai, Yusuke; Shimizu, Minami; Inoue, Komaki; Uehara‐Yamaguchi, Yukiko; Takahagi, Kotaro; Nakayama, Risa; Matsuura, Takakazu; Mori, Izumi C.; Hirayama, Takashi; Abdelsalam, Sobhy S. H.; Noutoshi, Yoshiteru; Mochida, Keiichi
SUMMARY: Rhizoctonia solani is a soil‐borne necrotrophic fungus that causes sheath blight in grasses. The basal resistance of compatible interactions between R. solani and rice is known to be modulated by some WRKY transcription factors (TFs). However, genes and defense responses involved in incompatible interaction with R. solani remain unexplored, because no such interactions are known in any host plants. Recently, we demonstrated that Bd3‐1, an accession of the model grass Brachypodium distachyon, is resistant to R. solani and, upon inoculation with the fungus, undergoes rapid induction of genes responsive to the phytohormone salicylic acid (SA) that encode the WRKY TFs BdWRKY38 and BdWRKY44. Here, we show that endogenous SA and these WRKY TFs positively regulate this accession‐specific R. solani resistance. In contrast to a susceptible accession (Bd21), the infection process in the resistant accessions Bd3‐1 and Tek‐3 was suppressed at early stages before the development of fungal biomass and infection machinery. A comparative transcriptome analysis during pathogen infection revealed that putative WRKY‐dependent defense genes were induced faster in the resistant accessions than in Bd21. A gene regulatory network (GRN) analysis based on the transcriptome dataset demonstrated that BdWRKY38 was a GRN hub connected to many target genes specifically in resistant accessions, whereas BdWRKY44 was shared in the GRNs of all three accessions. Moreover, overexpression of BdWRKY38 increased R. solani resistance in Bd21. Our findings demonstrate that these resistant accessions can activate an incompatible host response to R. solani, and BdWRKY38 regulates this response by mediating SA signaling. Significance Statement: Rhizoctonia solani  is a plant pathogenic fungus that causes sheath blight in grasses. In accordance with its necrotrophic lifestyle with a broad host range, the incompatible plant– R. solani interactions are not known in any host plants. Here, we demonstrate that such interactions could occur in the small grass Brachypodium distachyon, and BdWRKY38 is a key transcription factor that positively regulates this interaction by mediating the salicylic acid signaling pathway.